(untitled) (Estudios humanísticos. Geografía, historia y arte, 1994)
This article briefly relates the history of a small priory honouring Saint Felix at the beginning of the Tenth Century and located in a village called Saelices del Río, in the north and very Glose to Sahagún (León), whose large monastery of Saint Benito it depended for many centuries. We go over its history for more than one-thousand years fill its trasnfiguration into the current parish of Saint Felix.